Algoritma Support Vector Machine, Conditional Inference Trees, dan Random Forest untuk Klasifikasi Capaian Belajar Siswa SMP di Indonesia Tahun 2019 - Alfina Nurpiana; Arie Wahyu Wijayanto (Jurnal Matematika, Statistika dan Komputasi, 2022)
Indonesian JHS students' learning achievement is still low. During 2015-2019, the average national exam score for Indonesian JHS has always decreased. In the last national examination, the average national exam score was 52.82 and was included in the bad category. This certainly needs to be a concern for local governments and the education office. Therefore, it is necessary to form a classification model that can be used to identify cities/districts in Indonesia which are categorized as bad or enough. This study discusses the comparison of models for the classification of learning achievement categories as seen from the average 2019 JHS results in 514 districts/cities in Indonesia using the Support Vector Machine (SVM), Conditional Inference Trees (Ctree), and Random Forest (RF) algorithms. The three algorithms were chosen because of their respective advantages, namely the SVM algorithm is known to be very powerful, Ctree as an improvement from the usual decision tree, and RF to represent ensemble learning. The independent variables used are education budget, classroom conditions, school accreditation, and teacher qualifications. From the results of this study, it has been found that the SVM algorithm produces the highest accuracy (0,80), recall (0,97), kappa statistics (0,38), and F1-score (0,87) compared to the Ctree and RF algorithms, while only precision (0,80) has the same value as the Ctree algorithm. So, the SVM algorithm produces the best model for the classification of district/city learning achievement categories in Indonesia based on education budget, classroom conditions, school accreditation, and teacher qualifications.